Flow parameters in the vertebrobasilar system evaluated by Doppler ultrasonography in women and their dependence upon age - Stachowiak, Grzegorz; Stefańczyk, Ludomir; Mysior, Marek (Menopause Review/Przegląd Menopauzalny, 2002)
Objectives: to assess flow parameters in the vertebrobasilar system in women using Doppler ultrasonography and to evaluate dependence of changes in haemodynamics on age. Material and method: 314 women aged 18–72 (mean 49.8) free from cardiologic or neurologic disorders were examined between 1998–2001. The examinations of vertebral arteries were performed using Color-Coded option and linear probes 7–9 MHz (GE Logic 500) and 5 MHz (Acuson 128 XP-10). Peak-systolic (Vmax) and end-diastolic (Vmin) velocities were measured and resistance index (RI) was calculated. Patients were divided in 10-years groups and for each group mean values and standard deviation were assessed. Results: Flow velocities declined in consecutive age groups, decrease of Vmax predominated. The decline of Vmax was remarkable up to the age of 55 years (mean value from 84 cm/s in 18–25 group to 61 cm/s in 46–55 group). The resistance index declined with age, reaching its minimum of 0.67 (mean value) in 46–55 group. Conclusions: Flow velocities in vertebrobasilar system are age-dependent. Velocities decline with age, decrease of Vmax predominates. Resistance index is relatively high in young and elderly patients and reaches minimum in middle-age women.